2010
DOI: 10.1093/hmg/ddq272
|View full text |Cite
|
Sign up to set email alerts
|

The primate-specific microRNA gene cluster (C19MC) is imprinted in the placenta

Abstract: Imprinted genes play crucial roles in mammalian development and disruption of their expression is associated with many human disorders including tumourigenesis; yet, the actual number of imprinted genes in the human genome remains a matter of debate. Here, we report on the unexpected finding that the chromosome 19 microRNA cluster (C19MC), the largest human microRNA gene cluster discovered so far, is regulated by genomic imprinting with only the paternally inherited allele being expressed in the placenta. DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
282
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(301 citation statements)
references
References 92 publications
17
282
1
1
Order By: Relevance
“…In agreement with previous findings in other tissues 17 , the C19MC DMR exhibits hypermethylation in both normal and parthenogenetic PSCs, correlating with lack of expression of C19MC in PSCs (Fig. 2a-c).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous findings in other tissues 17 , the C19MC DMR exhibits hypermethylation in both normal and parthenogenetic PSCs, correlating with lack of expression of C19MC in PSCs (Fig. 2a-c).…”
Section: Resultssupporting
confidence: 93%
“…These results suggested that similar to many other imprinted genes, anti-miR-371-3 may be regulated in cis by a distant-imprinted DMR 1,16 . The miR-371-3 locus resides in proximity to the large miRs cluster C19MC, previously shown to ARTICLE be expressed exclusively from the paternal allele in the placenta 17 ( Fig. 2a).…”
Section: Resultsmentioning
confidence: 86%
“…Many imprinted genes are associated with an "imprinting control region" (ICR), the methylation of which regulates monoallelic gene repression. For example, two large micro-RNA clusters (C14MC and C19MC) on chromosome 14 and 19 are each regulated by an ICR such that both alleles are methylated and repressed in somatic tissues, but there is monoallelic DNA methylation of the ICR and expression of these microRNAs in placental tissues (Noguer-Dance et al 2010;Mouillet et al 2011). As previously mentioned, the DNA…”
Section: Monoallelic Methylation and Genomic Imprintingmentioning
confidence: 99%
“…The Sfmbt2 cluster expansion in mouse may additionally provide a useful model for other species-and lineage-specific miRNA expansions. For instance, in humans, an analogous primate-specific miRNA expansion is present on Chromosome 19 (C19MC), with a total of 46 miRNAs within a 100-kb interval being processed from the highly repetitive intron of a maternally imprinted placental noncoding RNA (45,46). In addition to a number of novel, primate-specific seeds, this cluster includes miRNAs with the seed "AAGUGC," found in miR-371-373 (the human counterpart of the miR-290-295 cluster) (47).…”
Section: Discussionmentioning
confidence: 99%